APPLICATION OF ARTIFICIAL BEE COLONY ALGORITHM TO AUTO-TUNING OF STATE FEEDBACK CONTROLLER FOR DC-DC POWER CONVERTER - Tarczewski, Tomasz; Niewiara, Łukasz J.; Grzesiak, Lech M. (Power electronics and drives, 2016)
The article presents an auto-tuning method of state feedback voltage controller for DC-DC power converter. The penalty matrices employed for calculation of controller’s coefficients were obtained by using nature-inspired artificial bee colony (ABC) optimization algorithm. This overcomes the main drawback of state feedback control related to time-consuming trial-and-error tuning procedure. The optimization algorithm takes into account constraints of selected state and control variables of DC-DC power converter. In order to meet all control objectives (i.e., fast voltage response and chattering-free control signal) an appropriate performance index is proposed. Proper selection of state feedback controller (SFC) coefficients is proven by simulation and experimental tests of DC-DC power converter.